2020
DOI: 10.1093/molbev/msaa122
|View full text |Cite
|
Sign up to set email alerts
|

The Architecture of Metabolism Maximizes Biosynthetic Diversity in the Largest Class of Fungi

Abstract: Abstract Ecological diversity in fungi is largely defined by metabolic traits, including the ability to produce secondary or “specialized” metabolites (SMs) that mediate interactions with other organisms. Fungal SM pathways are frequently encoded in biosynthetic gene clusters (BGCs), which facilitate the identification and characterization of metabolic pathways. Variation in BGC composition reflects the diversity of their SM products. Recent studies have document… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 108 publications
0
38
0
Order By: Relevance
“…We combine here our results with those of Watanabe and Townsend [75], Armaleo et al [10], Feng et al [12], Lünne et al [48], and Kealey et al [18], to provide an updated scheme of orcinol depside and depsidone synthesis, using as example the synthesis of olivetoric acid and physodic acid. We limit our description to orcinol lichen compounds as we do not yet know how many of the same rules apply to ß-orcinol depsides and depsidones.…”
Section: An Updated Scheme Of Orcinol Depside and Depsidone Synthesismentioning
confidence: 73%
“…We combine here our results with those of Watanabe and Townsend [75], Armaleo et al [10], Feng et al [12], Lünne et al [48], and Kealey et al [18], to provide an updated scheme of orcinol depside and depsidone synthesis, using as example the synthesis of olivetoric acid and physodic acid. We limit our description to orcinol lichen compounds as we do not yet know how many of the same rules apply to ß-orcinol depsides and depsidones.…”
Section: An Updated Scheme Of Orcinol Depside and Depsidone Synthesismentioning
confidence: 73%
“…Across 96 xylarialean genomes we predicted a total of 6,879 putative SMGCs (belonging to 3,313 cluster families) and 973 putative CGCs (belonging to 190 cluster families) (Supplementary Tables 3,4). In comparison, recent large-scale analyses predicted 3,399 SMGCs (in 719 cluster families) across 101 Dothideomycetes genomes 28 and 1,110 CGCs across 341 fungal genomes 29 . Only 25% of predicted SMGCs (n = 1,711, belonging to 816 cluster families) had BLAST hits to 168 unique MIBiG 30 accession numbers (Supplementary Table 3b).…”
Section: Xylariaceae and Hypoxylaceae Genomes Contain Hyperdiverse Metabolic Gene Clustersmentioning
confidence: 89%
“…are associated with virulence, except for pyranonigrin E, which is found only in A. phaeospermum. A previous study has suggested that alternapyrone and dimethylcoprogen play roles in plant pathogenesis (Gluck-Thaler et al, 2020). Dimethylcoprogen, a fungal extracellular siderophore, was reported to be responsible for the pathogenicity of Alternaria alternata to citrus (Chen L. H. et al, 2014).…”
Section: Discussionmentioning
confidence: 99%